Intellectual Invasion and Its Impact on Islamic Heritage. - Asma Abdul Aziz Abdullah (Zanco Journal of Human Sciences, 2025)
The phenomenon of intellectual invasion is not the result of the hour, but rather extends over hundreds of years. If it goes back to the apparent level, we would find it. In the era of the Prophet, it goes back to the days of prophecy. Since the dawn of Islam, Muhammad, may God’s prayers and peace be upon him, lusted for soothsayers and magicians, and the Messenger, may God’s prayers and peace be upon him, was based on what he saw from his people, giving them advice. In the civil era, the Jews confronted the Arab Muslims with different colors and various means of machinations, and they used the alien method of intellectual invasion represented by hypocrisy.